(untitled) - Harnack, Adolf von; (1851-1930) (U.S.A., 1981)
Careful scholarship and insightful commentary characterize this seminal treatment of the teachings of the church lathers concerning the military question. This first English translation of the now classic work includes an introduction which reviews the research since Harnack. The first chapter deals with the use of military terms and images in the New Testament and early Christian writings, and the effects this usage had on the behavior and attitudes of the church (for example, the issue of `holy war`). The second chapter reviews the sources to determine to what extent early Christians participated in the military and what judgments the church made on participation in warfare. The work also suggests how the apocalyptic mentality may have helped to legitimate participation in military activities and provides insight into how the early church came to terms with the problem of continuing life in the world.
Keywords: War -- Religious aspects -- Christianity History of doctrines -- Early church, ca 30-600